Quality of animals in GLP studies (Journal of Laboratory Animal Science, 2024)
GLP is a Quality system concerned with the organizational process and the conditions under which non-clinical health  and environmental safety studies are planned, performed, monitored, recorded, reported and archived. The purpose  of studies on “non-clinical health and environmental safety” is to investigate the physical/chemical, biological and/ or toxicological properties of the test item under investigation. The GLP principles are not only concerned about the  possibility for checking back the identity of the test item but also ensures that the correct test item has been applied  to the test systems. Test system characterization is an important quality control criterion in GLP studies. Regulators  need sound, healthy, valid, unbiased test systems, to obtain reproducible, repeatable and reliable test results. This is  possible only when we use properly characterized, pure, healthy test systems at a globally harmonized environmental  conditions.
Keywords: GLP studies; test systems; genetic monitoring; microbial monitoring; parasites monitoring